2019
DOI: 10.1371/journal.pone.0216133
|View full text |Cite
|
Sign up to set email alerts
|

Demographical, hematological and serological risk factors for Plasmodium falciparum gametocyte carriage in a high stable transmission zone in Cameroon

Abstract: Presence of mature gametocyte forms of malaria parasites in peripheral blood is a key requirement for malaria transmission. Yet, studies conducted in most malaria transmission zones report the absence of gametocyte in the majority of patients. We therefore sought to determine the risk factors of both all-stage and mature gametocyte carriage in an area with high stable transmission of Plasmodium falciparum in Cameroon. Gametocyte positivity was determined using three complementary methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Multivariate logistic regression analysis also revealed that being a pupil was a possible determinant of malaria infection in Nkongho-mbeng. Similar findings have been reported elsewhere [ 35 , 36 ]. This could be as a result of pupils constantly playing around the malaria vector breeding site, hence constantly exposed to the vector.…”
Section: Discussionsupporting
confidence: 93%
“…Multivariate logistic regression analysis also revealed that being a pupil was a possible determinant of malaria infection in Nkongho-mbeng. Similar findings have been reported elsewhere [ 35 , 36 ]. This could be as a result of pupils constantly playing around the malaria vector breeding site, hence constantly exposed to the vector.…”
Section: Discussionsupporting
confidence: 93%
“…The study area has been described previously. 27 Briefly, the health district of Esse is an eco-geographically and epidemiologically homogeneous area consisting of 54 villages with the inhabited zones mostly structured as clusters of houses. As in all neighboring communities in Yaounde, malaria transmission in the Esse health district is perennial and hyperendemic with entomological inoculation rates of 0.7-1.4 infected bites per person per month, 28 and with P. falciparum as the predominant plasmodial species.…”
Section: Methodsmentioning
confidence: 99%
“…While it is true that increased gametocytogenesis has been correlated with SFM, specifically with patterns of increased host immunity, severe anemia, and induced reticulocytosis [ 12 , 13 , 14 , 15 , 16 ], the presence of gametocytes does not always predict successful transmission to mosquito vectors. Further, while malarial gametocytemia has been positively correlated with mosquito infectivity [ 17 , 18 , 19 ], gametocyte commitment can occur without the maturity to infectious stage V gametocytes, and gametocytemia is not the only predictor of mosquito infectivity [ 20 , 21 , 22 , 23 ]. In this context, we sought to test the hypothesis that malaria-associated changes to circulating histamine in host blood and its effects on mosquito biology could facilitate successful infection of anopheline mosquitoes by gametocytemic blood.…”
Section: Introductionmentioning
confidence: 99%